Formation of emotional intelligence in the process of preparation of future social professionals in higher education institutions - Gren, L. M.; Kirsanov, Ivan (Національний технічний університет "Харківський політехнічний інститут", 2023)
The article emphasizes the importance of the role of education as one of the main components of supporting the transition period of Ukraine on the way to the EU and NATO; it has been proven that the formation of a new philosophy of higher education is simultaneously connected with emotional intelligence, which is of great importance in the training of future specialists in the social sphere in institutions of higher education. It was determined that the state and development of the modern Ukrainian economy depends on the quality of personnel training provided by universities. It was found that the lack of management culture, the insufficient level of moral and ethical training of specialists in the social sphere and qualified specialists in the field of professional ethics is an obstacle to the creation of an emotional and ethical infrastructure in Ukraine. The opinion is substantiated that the wide application of active learning methods with the analysis of real and educational business situations and the regular professional practice of future specialists in the social sphere at enterprises, firms, state authorities and local governments will ensure the effectiveness of the training of specialists in the social sphere, will contribute to the formation and development of ethical norms and emotional intelligence.

У статті наголошується на важливості ролі освіти як однієї з головних складових підтримки перехідного періоду України на шляху до ЄС і НАТО; доведено, що формування нової філософії вищої освіти безпосередньо пов'язане з емоційним інтелектом, який має велике значення у підготовці майбутніх фахівців соціальної сфери у закладах вищої освіти. Визначено, що стан і розвиток сучасної української економіки залежить від якості підготовки кадрів, яку здійснюють університети. З'ясовано, що гальмом у створенні емоційно-етичної складової інфраструктури в Україні є відсутність управлінської культури, недостатній рівень морально-етичної підготовки спеціалістів соціальної сфери та кваліфікованих спеціалістів у сфері професійної етики. Обґрунтовано думку, що широке застосування активних методів навчання з аналізом реальних і навчальних бізнес-ситуацій та регулярна професійна практика майбутніх спеціалістів соціальної сфери на підприємствах, фірмах, у державних органах влади та місцевого самоврядування забезпечить ефективність підготовки фахівців соціальної сфери, сприятиме формуванню та розвитку етичних норм та емоційного інтелекту.
Формування емоційного інтелекту у процесі підготовки майбутніх фахівців соціальної сфери у закладах вищої освіти
Keywords: emotional intelligence; social specialist; professional training; managerial culture; higher education; teaching methods; емоційний інтелект; спеціаліст соціальної сфери; професійна підготовка; управлінська культура; вища освіта; методи навчання